INVESTIGATION OF THE ONSHORE EXTENSION OF PENYU BASIN UNDERNEATH PEKAN, PAHANG: EVIDENCE FROM GRAVITY, MAGNETIC AND SEISMIC - MOHD MAZLAN, MUHAMMAD RADZIAMIR (2020)
The aim of this study is to model a possible onshore extension of the Penyu Basin underneath Pekan, Pahang by implementing integration of different geophysical methods. Three types of geophysical methods that were carried out in this research are gravity, magnetic and seismic refraction. The study area, which is in Pahang River Delta in Pekan, Pahang was chosen based on a theory whereby the west end of Penyu Basin may be situated in this coastal marginal sedimentary basin. Data analysis that was involved in this study included the reductions of old and new gravity and magnetic data, and processing of seismic data. Analysis of the data was carried out manually using Excel and by using specific geophysical software such as Oasis Montaj™ and Geogiga. In data interpretation section, it is divided into qualitative and quantitative analysis.